A specific inhibitor of polo-like kinase 1, GSK461364A, suppresses proliferation of Raji Burkitt's lymphoma cells through mediating cell cycle arrest, DNA damage, and apoptosis. (1st December 2020) - Ergul, Mustafa; Bakar-Ates, Filiz
Abstract: Polo-like kinase 1 (PLK1) is a prominent mediatory player during the cell cycle, mitosis, and cytokinesis in eukaryotic cells. Besides its physiological roles, PLK1 expression is upregulated in a wide range of human malignant tumors and its overexpression worsens prognosis, therefore, specific inhibition of PLK1 in tumor cells is a fascinating approach for the development of novel chemotherapeutics. The present study elucidated the potential cytotoxic effects of a PLK1 inhibitor, GSK461364A, in five cancer cell lines including Raji, K562, PC3, MCF-7, MDA-MB-231, along with noncancerous L929 cells by XTT assay. The cells were treated for 24 h with GSK461364A at different concentrations ranged between 0.5 and 40 μM and significant cytotoxicity was observed in all treated groups with the IC50 values between 2.36 and 4.08 μM. GSK461364A was also found to be safer with lower cytotoxicity against L929 cells and the IC50 value was found to be greater than 40 μM. Raji cells were identified as the most sensitive cell line against GSK461364A with the lowest IC50 values, hence it was selected for further studies to evaluate the underlying mechanism of cytotoxic activity. The treatment of Raji cells with GSK461364A caused a cell cycle arrest at the G2/M phase, also altered TOS, which is an indicator of oxidative stress, and DNA damage response, significantly. The Annexin V binding assay revealed that GSK461364A treatment significantly increased in the percentage of early and late apoptotic cells. Fluorescence imaging also showed that GSK461364A treatment significantly induced apoptosis of Raji cells. The apoptotic effect of the compound has also been confirmed by increased expressions of Bax and cleaved caspase 3 and along with the decreased expression of BCL-2. The results demonstrated that GSK461364A induced anticancer effects which was mainly promoted by cell cycle arrest, oxidative stress, DNA damage, and finally apoptosis in Burkitt's lymphoma cells. Taken together, the present results emphasized that GSK461364A could be a useful therapeutic agent in patients with Burkitt's lymphoma. However, further studies are required to consolidate the anticancer activity of this promising compound. Graphical abstract: Image 1 Highlights: GSK461364A evaluated for antiproliferative activity against Raji, K562, PC3, MCF-7, and MDA-MB-231 cell lines. GSK461364A exhibited the best cytotoxic activity against Raji cells. GSK461364A arrested the cells at G2/M-phase of the cell cycle and caused DNA damage. GSK461364A also induced apoptosis and altered total oxidant status (TOS) in Raji cells.